A STUDY ON THE STANDARDIZATION PARAMETERS OF MADHUCA LONGIFOLIA - Khare, Pragati; Kishore, Kamal; Sharma, Dinesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: There is an increase demand of herbal remedies due to their effective and safer way of treating various disorders. In today’s scenario, the herbal medicines are much efficient for the treatment of various disorders as they have minimal side effects in comparison to the allopathic medicines. Madhuca longifolia, commonly called Mahua/Mahwa, belongs to the family Sapotaceae. It grows up to a height of about 20 m. The objectives of this study are to investigate various pharmacognostic, phytochemical analysis, and pharmacological properties of M. longifolia. Methods: The powdered drug was used for estimating the loss on drying, ash values, fluorescence studies, chemical tests, and extractive values. Macroscopic and microscopic studies were also performed. Results: The leaf microscopy revealed the presence of upper and lower epidermis, palisade tissue, and well-developed vascular bundle. The fluorescence characteristics of leaf powder were studied both in visible light and ultraviolet (UV) light (254 nm and 365 nm) after treatment with various reagents. Mahua is composed of glycosides, sapogenins, steroids, saponins, flavonoids, and triterpenoids. It was reported that the total ash value was 5.56Â±0.2% w/w. The acid-insoluble and water-insoluble ash values were 0.62Â±0.025% w/w and 0.47Â±0.025% w/w, respectively. Water soluble, ethanol, methanol, petroleum ether, and chloroform extractive values were 25.9Â±0.51% w/w, 28.1Â±1.38% w/w, 1.73Â±0.20% w/w,0.83Â±0.20% w/w, and 25.5Â±2.29% w/w, respectively. Conclusions: The main pharmacological activities of M. longifolia are anthelmintic, antiulcer, antitumor, antimicrobial, antidiabetic, anti-inflammatory,antigoitrogenic, and hepatoprotective. The present investigation provides the information on its pharmacognostic, phytochemical analysis, and pharmacological properties.